GOOGLE SCHOLAR SEBAGAI SUMBER LITERASI DIGITAL DALAM MENULIS ARTIKEL ILMIAH DI PERGURUAN TINGGI - Lilis Amaliah Rosdiana; Vismaia S. Damaianti; Yeti Mulyati; Andoyo Sastromiharjo (Jurnal Semantik, 2024)
The purpose of this study is to determine the difficulties of students in academic writing and the role of Google Scholar as a source of digital literacy. The research used is descriptive research with a qualitative approach. The research was conducted on students of class 2020 of Winaya Mukti University who were taking 50 thesis courses. This study used data collection techniques, interviews and questionnaires. The results are the difficulties faced by students in academic writing, namely not optimal ability and knowledge in academic writing, students find it difficult to find ideas, ideas and topics in the academic writing they will write, students find it difficult to develop academic writing systematics, and students have difficulty getting references from the internet articles that match the topic they choose. Google Scholar is very important as a digital reference source in academic writing. With the existence of Google Scholar, students are greatly helped in finding reference sources, thousands of articles with the same topics as those chosen by students cause students to no longer have difficulty in developing ideas or ideas from scientific articles. The existence of Google Scholar is also seen as easy in terms of time and cost.